62.9k views
5 votes
3) z= m - x , for x
I need a answer

User PovilasB
by
5.6k points

2 Answers

4 votes

Hey there!☺


Answer:\boxed{x=m-z}


Explanation:


z=m-x

In our first step, we will flip the equation:


m-x=z

Now add -m to both sides of the equation:


m-x+-m=z+-m\\-x=-m+z

In our third/last step, we will divide both sides by -1:


(-x)/(-1)=(-m+z)/(-1)\\x=m-z

x=m-z is your answer.

Hope this helps!☺

User Tom Stock
by
4.5k points
4 votes

Answer:

-z+m=x

You subtract m, then divide z-m by -1.

User ManuKaracho
by
5.5k points